Análise de funcionalidade de pacientes submetidos à cirurgia cardíaca - Oliveira, Sofia Machado Nogueira de (2023)
Introduction: Cardiac surgeries are considered one of the main interventions to reduce symptoms and mortality in advanced heart diseases. In the postoperative period (PO), patients may have impairments that can affect different body segments in different ways, leading to reduced functioning in its various components (i.e., body functions, body structures, activities and participation). Objective: To analyze the behavior of functioning and its components in patients undergoing cardiac surgery. Methods: Observational and prospective study carried out at a University Hospital, from November 2020 to November 2022. Patients were evaluated in four moments: 1) preoperatively; 2) between the 4th and 6th PO day; 3) on the 30th PO day, and; 4) 30 days after hospital discharge. The following information were collected: general characteristics; lung function (ventilometry for slow vital capacity, SVC, and; maximum phonation time, MPT) and handgrip strength (HGS), as representatives of the body functions component; functional performance of upper limbs (number of repetitions in the 1-minute arm lifting test, 1MALT) and functional mobility (Timed Up & Go at maximum speed, TUGmax), as representatives of the activity component; and functioning (WHODAS 2.0) and healthrelated quality of life (HRQoL) (EQ-5D-5L), as representatives of the activities and participation components. Results: 85 patients hospitalized for elective cardiac surgery were assessed preoperatively, but only 35 completed all assessments (mean age 57±11 years, 21 women, mean ejection fraction 64±9%, 19 underwent myocardial revascularization). There was a reduction in SVC from pre to the 4th to 6th PO day, with improvement on the 30th PO, but without returning to baseline (p<0.001). There was a worsening of HGS and TUGmax from pre to the 4th to 6th PO day, with improvement on the 30th PO to values similar to baseline (p<0.001 for both). Between pre and 30 days after discharge, there was an improvement in the WHODAS 2.0 score, with a mean reduction of -9 (confidence interval – 95% CI -13, -5), and in the EQ-5D-5L index score, with a mean increase of 0.088 (95% CI 0.041, 0.135); p≤0.001 for both. WHODAS 2.0 score at preoperative assessment was the only variable to statistically explain the variation in change in its score from preoperative assessment to 30 days after discharge (r2=62%). Conclusion: Individuals who underwent cardiac surgery showed a reduction in lung function after surgery, which did not recover completely even 30 days after the procedure, but with recovery of the other functioning components evaluated to preoperative values. Even after this recovery, some functional components were still compromised 30 days after the procedure. Functioning assessed preoperatively was the only variable to explain the change from preoperative to post-hospital discharge.